Conceptual Understanding Of Mathematics Lesson With Classical Guidance Tutorial As A Final Examination Preparation On Grade 6 Lentera Harapan Elementary School- Tomohon - Nainggolan, D (Universitas Negeri Manado, 2019)
The research aim is to know how is the conceptual understanding of mathematics lesson with classical guidance tutorial as a final examination preparation on grade 6 Lentera Harapan Elementary School- Tomohon. The research was done by descriptive methods, with two (2) classes of Grade 6 students Lentera Harapan Elementary School- Tomohon. Data was collected through interviews and tests. Data analysis by using percentage of 40% students can get 6.5 KKM score (a minimum completeness criteria). This researches shows that in general student conceptual understanding of mathematics lesson is not satisfying. This is visible from 40% students ofÂ Grade 6 can understood the mathematics concept and 60% still struggling with the concept. The researcher discovered that there were misconception on fraction and memorizing on the units of length, time, weight and temperature and how to convert it on difference unit.Â Â Key words: Understanding, concept, mathematics